Evaluating the Impact of Conditional Cash Transfer Programs - Rawlings, Laura B. (Oxford University Press on behalf of the World Bank, 2013)
Several developing economies have recently introduced conditional cash transfer programs, which provide money to poor families contingent on certain behavior, usually investments in human capital, such as sending children to school or bringing them to health centers. The approach is both an alternative to more traditional social assistance programs and a demand-side complement to the supply of health and education services. Unlike most development initiatives, conditional cash transfer programs have been subject to rigorous evaluations of their effectiveness using experimental or quasi-experimental methods. Evaluation results for programs launched in Colombia, Honduras, Jamaica, Mexico, Nicaragua, and Turkey reveal successes in addressing many of the failures in delivering social assistance, such as weak poverty targeting, disincentive effects, and limited welfare impacts. There is clear evidence of success from the first generation of programs in Colombia, Mexico, and Nicaragua in increasing enrollment rates, improving preventive health care, and raising household consumption. Many questions remain unanswered, however, including the potential of conditional cash transfer programs to function well under different conditions, to address a broader range of challenges among poor and vulnerable populations, and to prevent the intergenerational transmission of poverty.